Use of Particle Agglutination in the Diagnosis of Dengue Virus Infection in Western Nepal - Pun, Ramesh; Pant, Krishna P; Shah, Yogendra; Sherchand, Shardulendra P; Pandey, Basu D (Nepal Journal of Science and Technology, 2012)
Dengue is an emerging vector borne viral disease in Nepal. The study was conducted to detect dengue virus specific IgM and to analyze demographic distribution of positive cases. This is a cross-sectional study carried out in western region of Nepal from August-October 2007. A total of 116 serum samples were collected from suspected dengue virus infected patients visiting hospitals and investigated by particle agglutination. Out of 116 sera, 12 (10.34%) had a positive dengue virus specific IgM. The positivity in age group below 15 years old was 23.08%, 7.32% in 15-50 years age group and 14.29% above 50 years age group. The ratio of positivity in male and female was 1:1. However, there were no statistical significance in the positivity with age (P=0.27) and sex (P=0.91). Thus, dengue has been established in western region of Nepal and diagnosis of the disease can be done by particle agglutination assay. The particle agglutination should be suggested for the diagnosis of dengue in all health centers of Nepal. Awareness programmes on prevention of dengue and surveillance of the disease should be conducted to reduce morbidity and mortality during possible outbreak of it. DOI: http://dx.doi.org/10.3126/njst.v12i0.6514 Nepal Journal of Science and Technology 12 (2011) 286-289